Citizen science projects require agreement: a Delphi study to identify which knowledge on urban ecology is considered relevant from scientists' and citizens' perspectives. Issue 1 (2nd January 2022) - Bruckermann, Till; Stillfried, Milena; Straka, Tanja M.; Harms, Ute
ABSTRACT: In citizen science (CS) projects, acquired knowledge about a specific topic is the most frequently acknowledged learning outcome. However, whether both citizens and scientists perceive the same knowledge to be relevant to citizens' learning in such projects remains unknown. Thus, establishing coherence between citizens' information needs and scientists' intentions to inform as well as exploring the reasons for why some knowledge is more relevant from citizens' and scientists' perspectives could help to achieve agreement regarding what knowledge is relevant for learning outcomes on the side of the citizens. By using the Delphi technique, we accounted for scientists' and citizens' perspectives on the relevance of knowledge in three fields of research on urban ecology. In our Delphi study, an emerging consensus indicated an overlap in relevance among the experts. We then analyzed two dimensions of relevance, that is, to whom and for what the knowledge is relevant. Our analyses of the dimensions revealed that consensus was more likely when we accounted for content-related differences and structural differences such as the communicatory perspective. When we accounted for content-related differences, relevance was higher for problem-oriented knowledge; therefore, this should be the focus of CS projects that are designed to achieve learning outcomes.